The Methodology of al-Tafsīr al-Mawḍū‘ī: A Comparative Analysis - El-Mesawi, Mohamed El-Tahir (Intellectual Discourse, 2005)
Abstract: The notion of thematic interpretation of the Qur’ān (al-tafsīr almawḍū‘ī) has attained a remarkable degree of conceptual and methodological clarity in the works of Muḥammad ‘Abd Allah Drāz, Muḥammad Maḥmūd Ḥijāzī, Muḥammad Bāqir al-Ṣadr and Fazlur Rahman. They provide cases that allow testing of methodological feasibility and intellectual fecundity of this approach to Qur’ānic exegesis. A common and important aspect of their works, as the textual analysis shows, is the attempt to search for a Qur’ānic conceptual framework for social theorization informed and guided by the fundamental Islamic world-view.